Análise do percurso do projeto "A criança entre nós" na produção da subjetividade de crianças diagnosticadas com transtorno do espectro autista em Manuas - AM - Lima, Salete da Silva (Brasil, 2024)
This research, approved by the Research Ethics Committee – CEP/UFAM, under number 6.416.032, maps the clinical-theoretical journey with two autistic children participating in the project “The child among us”, developed at the Applied Psychology Services Center – CSPA - from the Faculty of Psychology – FAPSI/UFAM. The work aimed to analyze the project's trajectory in the production of subjectivity of children diagnosed with autism spectrum disorder in Manaus – AM. The research is structured in a triple movement: the first, of a theoretical nature, focused on the notions of subject and subjectivity in the psychoanalytic field, whose construction is operationalized by the theses of Freud and Lacan; the second in the development of activities involving toys/games with a heterogeneous group of children (diagnosed with autism and typical); and third, the analysis of 6 (six) scenes of therapeutic management with 2 (two) autistic children. The methodology used was cartography, centered on Guattarian's conception of describing, intervening and creating subjectivity-effects at the same time. The result achieved was positive, confirming the research hypothesis that the psychoanalytic clinic enables the production of subjectivity in children diagnosed with autism.